Strategi Komunikasi Inovatif untuk Menjangkau Konsumen di Era Digital - Nurfatoni, M Mirza Hafif; Subhan, Roni (Ikatan Da'i Indonesia, 2024)
In the ever-evolving digital era, communication strategies have become crucial for effectively reaching consumers. This study aims to explore and analyze innovative communication strategies that can be used to engage consumers in the digital age. The research method employed is descriptive analysis and literature review to examine various communication strategies that have been implemented in the digital context. The findings of the study reveal that innovative communication strategies such as the utilization of social media, multimedia content, and voice recognition technology have a positive impact on fostering consumer engagement and expanding market reach. The key takeaway from this research is the significance of adapting to technological trends and developing communication strategies aligned with the preferences of digital consumers to enhance marketing effectiveness and boost business competitiveness. This study contributes to a deeper understanding of how communication strategies can be tailored to the digital era to achieve better marketing outcomes.